The Effectiveness of Law No 35 of 2014 Concerning Child Protection in Protecting Children’s Rights in the Educational Environment Using Analysis of Siyasah Dusturiyah (Case Study of Karo District) - Robby Surbakti, Aldi; Mora Matondang, Maulidya (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2023)
The current era of modernization makes children the nation’s successors who are required to become the next generation that can make Indonesia progress. One proof is that children are prepared to grow up to become the nation’s successors by providing protection from the government in protecting children’s rights and obligations as regulated in Law Number 35 of 2014. Ironically, the facts that occur in the field are not as expected by the community, as in many cases. Bullying that occurred in Karo Regency where the victim and perpetrator were still at school and even occurred in an environment where they were studying. This research uses a normative juridical approach and took place in Karo Regency using existing data from the Kabanjahe District Court and also from the Kabanjahe Religious Court. The results of this research explain that crimes against children where both the victim and perpetrator are minors in Karo Regency have occurred very frequently. In the school environment, there are also criminal acts of bullying, extortion, and assault. In this case, it could be said that the teacher can only advise students and not dare to give physical punishment to the perpetrator, which is why the implementation of Law No. 35 of 2014 is not effective. Because when the teacher gives a punishment the teacher will be afraid that the punishment violates the rules that have been set. This factor causes school children in educational environments to no longer have morals because they feel they are protected by law.